Enhanced photocurrent by the co-sensitization of ZnO with dye and CuInSe nanocrystals1. Issue 28 (28th July 2015) - Zhao, Jinjin; Wang, Peng; Wei, Liyu; Liu, Zhenghao; Zhang, Jiangbin; Si, Huayan; Mai, Yaohua; Fang, Xueqian; Liu, Xianglin; Ren, Deliang
<x xml:space="preserve">Abstract</x> ZnO@Cu0.28In1.72Se2.72 (5–10 nm) was synthesised for the first time using a template-free method and a vacuum one-pot-nanocasting process without long-chain ligands.